Heart rate variability: Response to graded head up tilt in healthy men - Sharma, P; Paudel, BH; Singh, PN; Linmbu, P (Kathmandu University Medical Journal, 2010)
Background: Heart rate variability is actually a misnomer for R to R variability in cardiac cycle. Variation in successive cycle length is called the heart rate variability (HRV). Head-up tilt is a model of studying cardiovascular haemodynamics, which reflects in heart rate variability (HRV). Objectives: To study the effect of 10° and 70° head-up tilt on HRV. Materials and methods: The study was done in the Department of Physiology using graded head up tilt (passive orthostatism). HRV measurement was done at 10° and 70° tilt and compared with supine using standardised methods on 30 consenting healthy males (age 25.37±3.89 years). The HRV variables across postures were compared by ANOVA and Bonferroni test. Results: The heart rate increased at 70° compared to 10° and supine (70.48±8.17 Vs 70.22±8.67 and 88.51±12.84 bpm, p<0.001). The 70° tilt decreased vagal HRV indicators compared to 10° and supine: SDNN (31.13±8.12 Vs 38.07±11.29 and 38.13±10.89 ms, p<0.05), RMSSD (20.06 ±8.47 Vs 34.23±14.22 and 36.16±12.22 ms, p<0.001), NN50 count (13.03±20.58 Vs 45.07±44.44 and 55.27±44.10, p<0.01), pNN50 (3.28±6.08 Vs 14.06±15.65 and 16.65±14.23, p<0.01), HF power (197.20±143.76 Vs 218.17±155.85 and 216.87±150.98 Hz, p<0.05), HFnu unit (24.28±14.16 Vs 45.48±16.34 and 47.67±19.89, p<0.001). The 70° tilt increased LF power% (197.20±143.76 Vs 218.17±155.85 and 216.87±150.98, p<0.001). LFnu unit (75.72±14.76 Vs 54.52±16.34 and 52.32±19.89, p<0.001), LF: HF (4.96±4.08 Vs 1.53±1.138 and 1.69±1.67, p<0.001) compared to 10° and supine. Conclusion: At 70° tilt, HRV measures, reflecting vagal contribution to cardiac-cycle length, decreased with reciprocal increase in sympathetic activity compared to 10° or supine leading to increase in sympathetic predominance. A 10° tilt, which is almost equivalent to lying down with pillow, did not change HRV from supine. Key words: Cardiac cycle; cardiovascular haemodynamics; head-up-tilt; heart rate variability; sympathetic activity; parasympathetic activity DOI: 10.3126/kumj.v7i3.2733 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 252-257